Profile of the Number of Patients With Chronic Pain Complaints in Kelurahan Pematang Pudu, Kota Duri, Kabupaten Bengkalis, Riau Province - Luthfi Ismi, Muhammad; Sitepu, John Frans (International Journal Labs, 2025)
Chronic pain is an unpleasant emotional or sensory experience that occurs continuously and persistently or often recurs for at least 3 months or more. Chronic pain is influenced by various factors such as biological, psychological and social factors that will continue to arise and it is not uncommon for patients with chronic pain complaints to experience pain that gets worse. Chronic pain is a health condition that has a wide impact on a person's quality of life, but even so data related to the prevalence of chronic pain in Indonesia is still very limited. Based on data collection in Pematang Pudu Village, there were 435 individuals aged 40 years and above experiencing chronic pain from May to October 2024. To identify patients with chronic pain complaints in Pematang Pudu Duri Urban Village, Mandau, Bengkalis, Riau. A quantitative descriptive research with a case series design, the sampling data collection technique is simple random sampling. The minimum sample size is 382 people using the sample size formula and using primary data collection techniques. Out of a total of 8262 individuals who met the inclusion criteria in the research, 435 people were found to have chronic pain which was dominated by 268 (61.1%) women while 167 people were men (38.4%). There are 435 individuals aged 40 years and above experiencing chronic pain in Pematang Pudu Village, Mandau, Bengkalis, Riau Province.